If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -2x + -13y + -7x + 6y = 0 Reorder the terms: -2x + -7x + -13y + 6y = 0 Combine like terms: -2x + -7x = -9x -9x + -13y + 6y = 0 Combine like terms: -13y + 6y = -7y -9x + -7y = 0 Solving -9x + -7y = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '7y' to each side of the equation. -9x + -7y + 7y = 0 + 7y Combine like terms: -7y + 7y = 0 -9x + 0 = 0 + 7y -9x = 0 + 7y Remove the zero: -9x = 7y Divide each side by '-9'. x = -0.7777777778y Simplifying x = -0.7777777778y
| 109=-8p-5(p-1) | | 8-3n+1n=7n-1 | | 5n-(-15n)= | | 6z-(z+1)+9= | | 2(9s+2)-10s=2(4s+1)-3 | | 8v+1=1-8v | | 2y=-7x+8 | | 7x+11y=16 | | 8(x+6)+3=51 | | (2xy-3x^2)dx+(x^2+y)dy=0 | | -(5y+2)-(-4y-4)=-2 | | 161+51(6)= | | y=1.90x+3.90 | | -16+4x=7x-5x | | 7x+11y=9 | | Xn=180(n-2) | | -5(v-4)+2=11-(v-3) | | x^2+20x+100-x^4=0 | | -5x+1+6x=-7+18 | | x^2+8x-9=-6 | | y-6+2(4y+2)=-5(y+4) | | 1.15z=61410 | | x+(x+1)+(x+2)+(x+3)+(x+4)+(x+5)=185 | | 12y=-96+8x | | 4(3a+4)-8= | | 4(4x-3)-6=12z-12-2x | | 60-5x=70-25x | | x(x-6)=14 | | -8x+2=8-6x | | -5(-3w+4)-7w=2(w-9)-5 | | (p^3-4p^2+p)-(3p^2+2p+7)=0 | | 4(a-8)=12a-6 |